Effectiveness of Early Versus Delayed Open Reduction and Internal Fixation for Isolated Mandibular Fractures - Muhammad Irfan Khan, Oam Parkash, Farah Irshad, Syed Aijaz Ali Zaidi, Sonam Nankani, Khursheed Ahmed (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Mandibular fractures are common maxillofacial injuries that can cause significant functional and esthetic impairments. Objectives: The main objective of the study is to find the effectiveness of early versus delayed open reduction and internal fixation for isolated mandibular fractures. Material and methods: This study is a retrospective analysis of patient conducted in Govt Lady Reading Hospital, Medical Teaching Institution, Peshawar, during January 2022 till December 2022 and data collected from medical records. The study compares the outcomes of early and delayed ORIF for isolated mandibular fractures. All patients who underwent ORIF for isolated mandibular fractures at a single institution over a two-year period were included in the study. Patients were excluded if they had associated injuries or comorbidities that could affect their outcomes or if they underwent surgery at another institution. Results: A total of 150 patients who underwent ORIF for isolated mandibular fractures were included in the study. Of these, 75 patients underwent early ORIF (within 72 hours of injury), and 75 patients underwent delayed ORIF (more than 72 hours after injury). The two groups were similar in terms of age, sex, and fracture type. Functional and esthetic outcomes were assessed using the Facial Disability Index and the Glasgow Benefit Inventory. The early ORIF group had a mean score of 75.2 on the Facial Disability Index, while the delayed ORIF group had a mean score of 68.9 (p < 0.05). Conclusion: In conclusion, this study suggests that early ORIF for isolated mandibular fractures may lead to better functional and esthetic outcomes compared to delayed ORIF, without increasing the risk of complications or healthcare costs.